2018
DOI: 10.18203/2320-1770.ijrcog20184970
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological evaluation of postmenopausal bleeding

Abstract: Background: Seventy percent of cases of postmenopausal bleeding have an innocent or harmless cause of bleeding but 30% of them are associated with malignancy. Hence it requires a thorough evaluation clinically and pathologically. As a considerable number of patients complaining of postmenopausal bleeding are reporting, the current study was undertaken to find out the incidence of the postmenopausal bleeding and the causes responsible for it.Methods: A hospital based cross sectional study was performed on women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Furthermore, the prevalence rate of postmenopausal bleeding among individuals aged over 60 years was found to be 20.55%. The findings of this study aligned with the results of prior studies by Agrawal et al (2018) andRita et al (2016). In the two studies, the prevalence rates of postmenopausal bleeding in women aged >50-60 years were found to vary between 48% and 67%.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, the prevalence rate of postmenopausal bleeding among individuals aged over 60 years was found to be 20.55%. The findings of this study aligned with the results of prior studies by Agrawal et al (2018) andRita et al (2016). In the two studies, the prevalence rates of postmenopausal bleeding in women aged >50-60 years were found to vary between 48% and 67%.…”
Section: Resultssupporting
confidence: 92%
“…A majority (56.16%) of the participants had an endometrial thickness of >10 mm, indicating a higher risk of malignancy. The investigations conducted by Agrawal et al (2018) and Rita et al (2016) reported prevalence rates of endometrial thickness of ≤5 mm as 44.87% and 52%, respectively. Furthermore, the two studies found that the prevalence rates of endometrial thickness exceeding 10 mm were 30.77% and 90%, respectively.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation